Prinsip Kesetaraan Hukum Dalam Islam: Studi Hadis Dan Penerapannya Dalam Sistem Hukum Tata Negara Di Indonesia - Imeilia, Tasya (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
This study analyzes the principle of equality before the law as taught in the hadiths of the Prophet Muhammad and evaluates its application in the context of modern society and judicial systems in majority-Muslim countries. The aim of this research is to understand the impact of these equality principles on the development of constitutional law and how they can strengthen the rule of law and social justice within governance systems. Through the analysis of hadiths, interpretations by scholars, case studies, and evaluation of legal practices, this research finds that the application of the principle of equality before the law can promote the creation of a more just and equitable legal system.